PANCARDI MAGMATISM AND STRUCTURE IN EARLY MESOZOIC - Pavliuk, M.; Medvedev, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Mesozoic magmatic formations on the territory of Ukraine occur in the basement of the trans-Carpathian basin, on the southern slope of the folded Carpathians, in the areas of Marmaros massif thrusting over Rakhiv and Burkut zones. These are not genetically uniform single sets of rocks, but rather the segments of tectonically and originally various complexes formed in the distinct tectonic environment on evolutionary differing crusts: continental crust (Vulkhovcici complex, picrite tuffs, Carpathian complex lavas); subcontinental crust (Trostianetskyi complex) and oceanic one (trans-Carpathian, Uholskyi, and Rakhiv-Chyvchynskyi complexes). Early Alpine structure of the Carpathians is not inherited from the previous stages; it resulted from the destruction of the earlier existing granite-metamorphic crust in the Early Mesozoic. Basic rocks in Rakhiv-Chyvchynskyi, Uholskyi, and the trans-Carpathian complexes have close chemical composition. These are mainly common basalts, sometimes subalkaline rocks or toleities, which belong to sodium (less commonly to sodium-potassium) series close to the oceanic toleities. They are likely to have formed druing undepleted mantle dissemination that had been partially differentiated. In Transylvanian ensimatic trough there formed Uholskyi ultramafic complex and Na-toleitic diabase. By microelements distribution Uholskyi complex is close to the standards of the upper mantle. Uholskyi ultramafic complex may represent fragments of the upper mantle protrusional outbursts. Similar rock complexes are known in other parts of PANCARDI. Rocks of differentiated Trostianetskyi complex belong to K-Na series of basalt-trachyte formation, which may have been as Rakhiv-Severyn ensialitic trough on the thinned continental crust in the Early Cretaceous. Rocks of Trostianetskyi complex are characterized by an increased degree of differentiation, subalkalinity, potassium-sodium series and increased aluminosity. The ensimatic troughs mentioned above are separated by thin blocks of continental crust represented by high pottasium trachyte-dolerites of Vulkhovcici complex and other units. The data analysis proposed a scheme of paleostructures in the continental crust and suggested a geodynamic model of the region. The EarlyAlpine structure is an area of crushed granite-metamorphic crust alterated by newly-formed oceanic crust. In the middle of Late Jurassic, there were present all ensimatic troughs with different geodynamic closures. By the end of the Early Cretaceous almost all ensimatic troughs had been closed and all Upper Cretaceous and Paleogene sediments were predominantly formed by compressional stresses.